Case Report: Report of Two Cases of Interstitial Lung Disease Caused by Novel Compound Heterozygous Variants in the ABCA3 Gene - Chen, Fang; Xie, Zhiwei; Zhang, Victor Wei; Chen, Chen; Fan, Huifeng; Zhang, Dongwei; Jiang, Wenhui; Wang, Chunli; Wu, Peiqiong (Frontiers in Genetics, 2022)
Interstitial lung disease (ILD) is a heterogeneous group of pulmonary disorders involving the lung interstitium and distal airways, also known as diffuse lung disease. The genetic defects resulting in alveolar surfactant protein dysfunction are a rare cause of ILD in pediatric patients. We report two unrelated pediatric patients with shortness of breath, dyspnea and hypoxemia, and the chest CT findings including patchy ground-glass opacity in both lung fields, suggestive of diffuse ILD. One patient was a full-term male infant who had shortness of breath a few hours after the birth, and then developed into severe respiratory distress syndrome (RDS). Whole exome sequencing revealed novel compound heterozygous variants in the ABCA3 gene (NM_001,089.3): paternally inherited c.4035+5G > A and c.668T > C (p.M223T), and maternally inherited c.1285+4A > C. The second patient was a 34-month-old boy with onset of chronic repeated cough and hypoxemia at 9 months of age. We unveiled novel compound heterozygous ABCA3 variants (c.704T > C, p.F235S; c.4037_4040del, p.T1346Nfs*15) in this patient. Surfactant protein dysfunction due to bi-allelic mutations in the ABCA3 gene was the cause of ILD in two patients. The novel mutations found in this study expanded the spectrum of known mutations in the ABCA3 gene.